2007
DOI: 10.2527/jas.2006-431
|View full text |Cite
|
Sign up to set email alerts
|

Sites of nutrient digestion in growing pigs: Effect of dietary fiber1

Abstract: The impact of dietary fiber on fecal digestion is well-known and provides a comprehensive approach toward nutrient digestibility and availability. Little quantitative information is available on digestion of fiber in the different segments of the gastrointestinal tract (GIT). The objectives of this study were to obtain a method allowing the quantification of the digestive process in different segments of the GIT and to study the impact of dietary fiber on nutrient digestibility. Six barrows (average initial BW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
73
1
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 40 publications
13
73
1
12
Order By: Relevance
“…Contrary were the results of other researchers (Landero et al, 2011;Moset et al, 2012) who observed that the addition of RSM in pigs' diets causes a significant reduction in the digestibility of nutrients, which is attributed to the increase in the proportion of CF in the faeces, and secondly because of increased water retention capability of the CF (Wilfart et al, 2007;Moset et al, 2012). This contradictory result is probably due to the limited feed intake in the present study.…”
Section: Apparent Digestibility Coefficientmentioning
confidence: 73%
See 2 more Smart Citations
“…Contrary were the results of other researchers (Landero et al, 2011;Moset et al, 2012) who observed that the addition of RSM in pigs' diets causes a significant reduction in the digestibility of nutrients, which is attributed to the increase in the proportion of CF in the faeces, and secondly because of increased water retention capability of the CF (Wilfart et al, 2007;Moset et al, 2012). This contradictory result is probably due to the limited feed intake in the present study.…”
Section: Apparent Digestibility Coefficientmentioning
confidence: 73%
“…In particular, the reduction of digestibility of energy potential is attributed to the reduction of digestibility of dry and organic matter of diets (Wilfart et al, 2007) or to the reduction of the digestibility of carbohydrates in diets (Le Gall et al, 2009), due to acidification of the digesta, which results in limited absorption of nutrients of the digesta by the epithelial cells of the intestinal tract (Rainbird et al, 1984). The decreased digestibility of CP and amino acids is possibly attributed to the restriction of their absorption and / or to increased concentration of endogenous N and thus to the loss of amino acids (Mosenthin et al, 1994).…”
Section: Apparent Digestibility Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of dietary fibre associated with bulkiness, i.e. gut fill, on retention time and nutrient availability are well documented (Shriver et al, 2003;Wilfart et al, 2007). Despite some negative impacts, farmers in tropical areas use fibrous crop by-products and forages extensively as alternatives to expensive cereals in pig diets.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sesuai dengan pendapat Jurkonski et al (2008) yang menyatakan bahwa partikel serat umumnya memiliki gugus penukar ion kation yang memiliki kemampuan seperti matriks spons untuk mengikat partikel lemak dengan ikatan intraluminal. Hasil ini sesuai dengan yang pernah dilaporkan oleh Wilfart et al (2007), bahwa peningkatan konsentrasi serat dalam ransum menyebabkan peningkatan kandungan ekstrak ether feses ternak babi.…”
Section: Karkas Ternak Babiunclassified